Respostas

2014-08-19T21:21:12-03:00
A^2= b^2 + c^2
(3x-11)^2 = (2x+3)^2 + (x-4)^2
(3x-11) (3x-11) = (2x+3) (2x+3) + (x-4) (x-4)
9x^2 -33x -33x +121= 4x^2 +6x +6x +9 + x^2 -4x -4x +16
9x^2 -4x^2 -x^2 -33x -33x -6x -6x +4x +4x +121 -9 -16= 0
4x^2 -70x +96 =0
a=4 b= -70 c=96
delta=(-70)^2 -4.4.96
delta= 4900 -1536
delta= 3364

x'= 70+58/8
x'= 128/8
x'= 16

x"= 70-58/8
x"= 12/8
x"=3/2 (não serve)

Cateto 1
2x+3
2.16+3
35

Cateto 2
x-4
16-4
12

Hipotenusa
3x -11
3.16-11
37

R) Perímetro= 35+12+37
    Perímetro= 84


4 3 4